Cultural Beats and Language Feats: Enhancing English Skills at @America through Jazz Music Festival - Lestari, Puji; Purwa Lestarina, Anggi; Ditha Berliana, Alya; Natalia, Inpresta; Resyta Arma, Ladie; Juwita, Rahma (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study explores how immersive language use and cultural exposure can enhance English as a Foreign Language (EFL) learning among Indonesian university students. It aims to identify the communicative benefits of participating in an interactive visit to @america, an American cultural center in Jakarta, and to examine how visual ethnography supports students’ reflections on intercultural learning. On December 3, 2024, one hundred EFL students attended the Empire Wild Jazz Music Festival at @america, engaging in authentic listening, speaking, and intercultural interaction under a Communicative Language Teaching (CLT) framework. Photographs and personal reflections served as primary data for the visual ethnographic analysis. The findings indicate that this informal, immersive environment increased students’ motivation, fostered fluency development, and deepened cultural awareness. The visual documentation process also encouraged students to critically reflect on their learning and cultural experiences. This study demonstrates that integrating experiential activities and visual reflection into EFL curricula can help educators bridge the gap between classroom instruction and real-life communication, ultimately enhancing students’ engagement and intercultural competence.